Perceived effect of the FDS seminars on familial relationship among Pantawid Pamilyang Pilipino Program (4PS) beneficiaries in Bay, Laguna, Philippines - Manguiat, Thessalonica S. (UP Los Baños Journal, 2018)
The Family Development Session (FDS), seminars for parent-beneficiaris, of the Pantawid Pamilyang Pilipino Program (4Ps) aims to promote positive family values and strengthen marital relationships, parental roles, and responsibilities. The study aimed to analyze the changes on the familial relationship of 4Ps beneficiaries which could be attributed to their attendance in FDS seminars. Simple random sampling was applied to select 84 respondents who were 4Ps parent-beneficiaries in Bay, Laguna. It utilized a mixed-method approach, employing a survey interview and focus group to gather data on the respondent's knowledge, attitude and practices on marital and parental relationships and children's behaviour. The contents of the questionnaire were designed to capture the principles taught in the Family Development Session Module called "Gabay sa Pagpapaunlad ng Pamilyang Pilipino". Descriptive statistics was used to describe the demographics, frequency of attendance to FDS, and knowledge of the respondents. Spearman's correlation was used to analyze the relationship between the demographic characteristics, frequency of attendance to FDS, knowledge, attitude, and practices of parent beneficiaries, and child's behavior. Wilcoxon Signed-Rank Test was used to examine score differences between "Before 4Ps" and "Now in 4Ps". Content analysis was used to examine the emerging themes from the qualitative responses. Findings show that the parent-beneficiaries were able to apply parental relationship lessons more than the marital relationship lessons. They became more responsive to their children's needs, positively affecting the children's behavior. Since FDS focuses more on child caregiving, it is recommended that marital and family relationship enrichments also be given emphasis.